PENERAPAN SCRAPBOOK DALAM PEMBELAJARAN MAHARAH KITABAH SISWA KELAS XI SMA ISLAM AL-ISLAH BUKITTINGGI - Fahmi Hafizha Oktoviari; Hurriyatus Sa’adiyah (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This research was motivated by the fact that Al-Islah Islamic High School, Bukittinggi, found that students were less interested in learning Arabic, especially in implementing the Bible. This is because teachers still use conventional models and methods in implementing learning, besides that teachers have not yet innovated and varied in developing learning media. So by looking at this, the researcher intends to use relevant media that can increase students' enthusiasm and interest by using scrapbooks. The type of research used is descriptive qualitative with data collection in the form of interviews, observation and documentation. Then the data is processed by data reduction, triangulation and then conclusions are drawn. The conclusion of this research is that the application of scrapbook media is able to increase students' interest in the Maharah Kitabah because of the attractiveness of the creativity used in this learning.